2018
DOI: 10.5578/fmbd.67275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Utilization of Ground Yellow Poppy Seed in Cracker Production on Some Physical Properties and Phenolic Content

Abstract: Bu çalışmada, sarı haşhaş ezmesi kullanılarak kraker üretilmiş ve haşhaş ezmesinin krakerlerin bazı fiziksel özellikleri ve fenolik madde içerikleri üzerine etkileri incelenmiştir. Sarı haşhaş ezmesi (Afyon), kraker formülasyonuna %10, %20 ve %30 oranlarında ilave edilmiştir. Üretilen krakerlerin ağırlığı, yüksekliği, renk değerleri (L*, a*, b*) ve toplam fenolik madde içeriği incelenmiştir. Kraker ağırlığı ve yüksekliği, sarı haşhaş ezmesi ilave edilen örneklerde kontrol örneğine kıyasla daha az bulunmuştur. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…(2012) reported that 1.0%, 3.0%, 5.0% and 7.0% concentrations of coriander leaf powder added to bread flour increased the antioxidant capacity of bread, and adding 3% and 5% improved bread quality. In previous study, As the poppy paste concentration of crackers made by adding yellow poppy seed paste at 10%, 20% and 30% concentrations increased, the L * value decreased, while an increase was monitored in the a * and b * results (Yalçın, 2018). In other study, L * values decreased from 73.14 to 29.25 with the addition of hemp flour to bread flour, while a * values increase from 0.85 to 3.36 (Mikulec et al ., 2019).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…(2012) reported that 1.0%, 3.0%, 5.0% and 7.0% concentrations of coriander leaf powder added to bread flour increased the antioxidant capacity of bread, and adding 3% and 5% improved bread quality. In previous study, As the poppy paste concentration of crackers made by adding yellow poppy seed paste at 10%, 20% and 30% concentrations increased, the L * value decreased, while an increase was monitored in the a * and b * results (Yalçın, 2018). In other study, L * values decreased from 73.14 to 29.25 with the addition of hemp flour to bread flour, while a * values increase from 0.85 to 3.36 (Mikulec et al ., 2019).…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, recently, studies are continuing to make bakery products healthier by enriching bakery products with functional components (Akhtar et al ., 2011; Raina et al ., 2023). In recent years, there has been an interest in the use of natural ingredients containing bioactive ingredients in bakery products, such as bread and crackers (Rozylo, 2013; Yalçın, 2018; Kaur et al ., 2023). The trend of enriching bread and bakery products with plant products, such as fruits and vegetables, has led to better knowledge about biological active constituents (Dziki et al ., 2014; Kaur et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%